The identity of the Italian in the evolution of the catenaccio (Impetus, 2021)
Catenaccio is clearly identified in Italian football, in all the world; It has been adopted by the Italians as a system attached to your culture. The mentality of the Italian retreat and be waiting to attack when the opponent is vulnerable, is a myth attributed to Gianni Brera, however, the Italians have done as yours which I dare say that the myth became reality. This perspective, sets a relation between the catenaccio and the dialectic of master and slave, which consists of the life and death struggle by recognizing another self-consciousness (any person who is in and for itself). The self-consciousness that yields in the struggle, for fear of death lost autonomy. However in that loss, there is the opportunity to achieve autonomy through work, which creates culture. Although the catenaccio is not Italian creation, and it was assumed as identity of the Italians, this tactical system has given bianconera self-consciousness (Juventus onomastico) desired recognition. This recognition is evident in the Italian soccer world; Juventus of Turin is the current representative of this recognition, and it is precisely this equipment which has acquired the success (recognition) by the 3-5-2 system, purely defensive system, which gives priority to effectiveness in the minimum difference.